Comparative Risk of Incident Cancer in Patients with Inflammatory Bowel Disease with Prior Non-digestive Malignancy According to Immunomodulator: a Multicentre Cohort Study. (5th May 2022) - Poullenot, F; Amiot, A; Nachury, M; Viennot, S; Altwegg, R; Bouhnik, Y; Abitbol, V; Nancey, S; Vuitton, L; Peyrin-Biroulet, L; Biron, A; Fumery, M; et al.
Abstract: Introduction: Knowledge about the cancer risk when initiating a biologic in inflammatory bowel disease [IBD] patients with prior malignancy remains scarce, especially for vedolizumab. Our aim was to evaluate the rate of incident cancer in a cohort of IBD patients with prior non-digestive malignancy, according to the subsequent treatment given. Methods: A multicentre retrospective study included consecutive IBD patients with prior non-digestive malignancy. Inclusion date corresponded to the diagnosis of index malignancy. Patients were categorized into different cohorts according to the first treatment [none, conventional immunosuppressant, anti-TNF, or vedolizumab] to which they were exposed after inclusion and before incident cancer [recurrent or new cancer]. Results: Among the 538 patients {58% female; mean (standard deviation [SD]) age inclusion: 52 [15] years} analyzed, the most frequent malignancy was breast cancer [25%]. The first immunomodulator given after inclusion was a conventional immunosuppressant in 27% of patients, anti-TNF in 21%, or vedolizumab in 9%. With a median (interquartile range [IQR]) follow-up duration of 55 [23-100] months, 100 incident cancers were observed. Crude cancer incidence rates per 1000 person-years were 47.0 for patients receiving no immunomodulator, 36.6 in the anti-TNF cohort, and 33.6 in the vedolizumab cohort [ p = 0.23]. Incident-cancer free survival rates were not different between patients receiving anti-TNF and those receiving vedolizumab [ p = 0.56]. After adjustment, incidence rates were not different between patients receiving no immunomodulator, anti-TNF, or vedolizumab. Conclusions: In this large multicentre cohort study, there was no difference of cancer incidence in those IBD patients with prior non-digestive malignancy, treated with vedolizumab or anti-TNF.